2019
DOI: 10.15388/infedu.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Model Application Using Accessible Learning Objects to Support the Teaching of Mathematics

Abstract: This article presents an experience report regarding the application of an Inclusive Model of Development of Accessible Learning Objects, in the Mathematics discipline, to help 8th year Elementary School children, to perform calculations with natural numbers. The Learning Object was developed using Scratch and accessibility guidelines to include students with disabilities. The model evaluated the learning, teaching, usability, and accessibility of objects. The results demonstrate the efficiency, interaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…For example, transcription and closed captioning of online videos were originally used to make content accessible to the deaf and hard of hearing. However, nowadays, this technology is successfully employed and enjoyed by other groups, such as people who want to learn a second language, people with dyslexia, and seniors [12].…”
Section: Related Workmentioning
confidence: 99%
“…For example, transcription and closed captioning of online videos were originally used to make content accessible to the deaf and hard of hearing. However, nowadays, this technology is successfully employed and enjoyed by other groups, such as people who want to learn a second language, people with dyslexia, and seniors [12].…”
Section: Related Workmentioning
confidence: 99%
“…Reusability eliminates the need to create new objects each time, lowering costs and increasing productivity. (Ho, 2021), (Mourão & Netto, 2019) A learning object, according to the International Society for Technology in Education (ISTE), is any digital or non-digital object that supports the learning process and can be customized to the needs of a group of learners and reused in other learning situations. Also, it can define them as "digital learning units that contain small particles of educational content prepared in a digital form, address a specific goal, and can be reused in another educational situation.…”
Section: Concept Of Learning Objectsmentioning
confidence: 99%
“…The interactive learning objects are appreciated by many instructors in search of new methods and supports for novice programming students (Matthiasdottir, 2006). Several studies showed that the use of learning objects contributes significantly to the improvement of computer science teaching-learning process (Adamchik & Gunawardena, 2003;Andreza & Magalhães, 2019;Begosso et al, 2015;Cavus & Ibrahim, 2004; Jaimez-González, García-Mendoza, Luna-Ramírez, Nápoles-Duarte, & Vargas-Vargas, 2018; Luna-Ramírez & Jaimez-González, 2014; Narasimhamurthy & Shawkani, 2009;Tapoli & Mikropoulos, 2019;Villalobos & Jiménez, 2009).…”
Section: Litreture Reviewmentioning
confidence: 99%